Analysis of English Registers in Pilates Practice - Luthfi Nurhaliza (Critical Review of English-Arabic World Journal, 2026)
This study aims to analyze the use of English language registers in Pilates practice, particularly in interactions between instructors and participants. This research was conducted to examine the application of English language registers used in Pilates activities, especially during interactions between instructors and participants. The scope of the study includes the forms of these registers, their linguistic functions, and the situational contexts that influence their use. A descriptive qualitative approach was employed as the research method, utilizing observation and discourse analysis techniques, while the data collected consisted of utterances by Pilates instructors containing technical and instructional terms in English. The study reveals that anatomical terms, muscle activation, movement instructions, and breathing instructions dominate the use of these registers. These terms serve to provide guidance, ensure safety during each movement, and enhance the overall efficiency of the exercise.